Transarterial venous sinus occlusion of dural arteriovenous fistulas using ONYX - Torok, Collin M (Interv Neuroradiol, 2016)
PURPOSE: The purpose of this article is to present a case series of transarterial venous sinus occlusion for dural arteriovenous fistulas (DAVFs) of the transverse and sigmoid sinuses. MATERIALS AND METHODS: From 2006 to 2012, 11 patients with DAVF of the transverse and sigmoid sinuses were treated with transarterial closure of the affected venous sinus using ethylene vinyl alcohol copolymer (ONYX). The consecutive retrospective cohort included six female and five male patients with an age range of 30–79. Patients presented with stroke, intracranial hemorrhage, seizure, headache, focal neurologic deficit or cognitive change. Lesions were categorized as Cognard II a + b (n = 5) or Cognard II b (n = 6). Four of this latter group consisted of isolated sinus segments. Selection criteria for dural sinus occlusion included direct multi-hole fistulas involving a broad surface in length or circumference of the sinus wall. External carotid artery (ECA) branches were directly embolized when considered safe. High-risk arterial supply from ICA, PICA, AICA or ECA cranial nerve branches were closed via retrograde approach during sinus occlusion. RESULTS: DAVF closure was accomplished in all 11 patients with a total of 17 embolization procedures using ONYX. High-risk arterial collaterals were closed via artery-artery or artery-sinus-artery embolization. The vein of Labbe was spared in the four cases with initial antegrade flow. No neurologic complications occurred, and DAVF closures were durable on three-month angiography. CONCLUSION: Transarterial closure of the transverse and sigmoid sinuses.